Microbial Growth on C1 Compounds 1996
DOI: 10.1007/978-94-009-0213-8_31
|View full text |Cite
|
Sign up to set email alerts
|

Production of L-Lysine and Some Other Amino Acids by Mutants of B. methanolicus

Abstract: INTRODUCTION:Bacillus methanolicus is is a Gram-positive, endosporeforming, facultative methylotroph with an optimal growth temperature of 50-53 0 C. This bacterium employs the efficient ribulose-monophosphate pathway for formaldehyde assimilation and possesses a novel nicotinamide adenine nucleotide-dependent methanol dehydrogenase (Dijkhuisen et ai, 1988) rather than the cytochrome linked MDH found in gram-negative methylotrophs. Several isolates similar to those isolated by us (Schendel et ai, 1990) have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 14 publications
0
18
0
1
Order By: Relevance
“…We therefore proceeded to analyze transcription levels for the aspartate pathway genes in this mutant by using RT-PCR as described above. To obtain comparable conditions for growth, cells were cultivated in methanol medium supplemented with 1 mM DL-methionine and 1.5 mM L-threonine (see Materials and Methods), as required for growth of NOA2#13A52-8A66 (19). Both MGA3 and M168-20 were included as control strains, and the results of these experiments are shown in Table 4.…”
Section: Resultsmentioning
confidence: 99%
“…We therefore proceeded to analyze transcription levels for the aspartate pathway genes in this mutant by using RT-PCR as described above. To obtain comparable conditions for growth, cells were cultivated in methanol medium supplemented with 1 mM DL-methionine and 1.5 mM L-threonine (see Materials and Methods), as required for growth of NOA2#13A52-8A66 (19). Both MGA3 and M168-20 were included as control strains, and the results of these experiments are shown in Table 4.…”
Section: Resultsmentioning
confidence: 99%
“…B. methanolicus uses an NAD(P)-dependent methanol dehydrogenase (MDH) to oxidize methanol to formaldehyde, and in addition to entering the RuMP pathway, a linear branch for dissimilation of formaldehyde to CO 2 was recently demonstrated (29). It was previously shown that this bacterium can secrete 55 g of glutamate per liter at 50°C by using methanol as a carbon source in fed-batch fermentation (11), and a homoserine dehydrogenase mutant (13A52-8A66) that secreted up to 35 g of L-lysine per liter at 50°C was described (18). In a previous study (13) it was found that the B. methanolicus NOA2 mutant 13A52 possesses a plasmid with an estimated size of 17 kb, and a plasmid of a similar size was later identified (N. Tsujimoto, H. Yasueda, and S. Sugimoto, 24 October 2000, Japanese patent application JP2000295988) in B. methanolicus PB1 (ϭ NCIMB 13113).…”
mentioning
confidence: 99%
“…The gram-positive and thermotolerant methylotroph Bacillus methanolicus has been studied as an alternative producer of L-glutamate and L-lysine using methanol as the raw material (for a review, see reference 5). We have previously demonstrated that wild-type B. methanolicus produces 58 g/liter of L-glutamate (6), while mutants generated by random chemical mutagenesis have been reported to produce up to 37 g/liter of L-lysine (16,23,34). Favorable properties of B. methanolicus, such as a lack of sporulation at high temperatures, utilization of methanol as an energy and carbon source, a high methanol conversion rate, a high theoretical yield of L-lysine, and an optimal growth temperature of 50°C, indicate that this organism may represent a possible future noncarbohydrate substrate alternative for large-scale production of L-lysine (5).…”
mentioning
confidence: 99%